Desenvolvimento de imunossensores fotoeletroquímicos para detecção de Leishmania (L.) infantum - YOTSUMOTO NETO, Sakae (2019)
This work describes the development of photoelectrochemical immunosensors for the detection of anti-Leishmania infantum antibodies. The first one is based on electrodeposited zinc oxide and cadmium sulphide films on indium tin oxide coated glass slide (CdS/ZnO/ITO). The effects of the light/dark and regeneration kinetics of CdS sensitizer was evaluated by scanning electrochemical microscopy in feedback mode. The platform was modified by using two different peptides (PEP 13 and PEP 16) from two different proteins of high specificity and selectivity in recognition of L. infantum antibodies, which was henceforward denoted as Peps/CdS/ZnO/ITO. The proposed photoelectrochemical immunosensor is a cheap and promising alternative to discriminate positive and negative canine serum samples. The second one describes the development of a high sensitive photoelectrochemical immunosensor for the detection of anti-Leishmania infantum antibodies. The proposed sensor is based on recombinant L. infantum antigens and cadmium sulphide films sensitized with gold nanoparticles deposited on indium tin oxide coated glass slide (AuNP/CdS/ITO). The bandgap and flatband characteristics of AuNP/CdS platform were evaluated by UV-Vis spectrophotometry and electrochemical impedance spectroscopy. The effects of the nature, concentration and pH of the buffer solution as well as the effects of the applied potential on the response of photoelectrochemical platform to a donor molecule were also investigated. Under optimized conditions, the AuNP/CdS/ITO platform modified with recombinant L. infantum antigens (C8/MPA-AuNP/CdS/ITO) shows a linear response range from 1 up to 300 nmol L-1 to anti-C8 antibodies. Finally, the capability of the proposed photoelectrochemical immunosensor to discriminate positive and negative canine serum samples was evaluated in real canine serum samples. CdS films obtained by chemical bath deposition were applied to positive and negative canine samples aiming the evaluation of photoelectrochemical devices as auxiliary systems for clinical assays. The L. infantum (C8) recombinant antigens modified CdS photoelectrochemical platform presented clinical selectivity and sensitivity of 96% and 88%, respectivelly.